El estado actual del mercado laboral en la Región de Puno y sus desafíos - Milla Canales, Gustavo (2024)
The city of Puno located in the South East of Peru at an altitude of 3,827 meters above sea level, 1,354 km away from the city of Lima, presents a great challenge to recover its labor market and improve its economy, which has recently been affected by two events that their activities were reduced: The presence of the pandemic due to the new coronavirus and the recent social conflicts due to the fragile political situation that currently affects the country. In both cases, these events have brought serious losses to their economy, which was reflected in unemployment, informality, increased crime, and vandalism. Added to this are the effects of global warming, the current global boil, and the drought that, due to a lack of rain, has caused in recent years the loss of 4 meters in the water level of Lake Titicaca, which could also bring with it substantial million-dollar losses for livestock, agricultural, fishing, and mining production, which would significantly affect employment in this region.   The objective of this research is to explain and generate a series of strategies to revive the labor market and develop the economic flow, which reactivates employment in this department, which will be beneficial for the growth and development of its population.